Orchestrated feedback regulation between melatonin and sex hormones involving GPER1‐PKA‐CREB signaling in the placenta - Shao, Xuan; Yang, Yun; Liu, Yanlei; Wang, Yongqing; Zhao, Yangyu; Yu, Xin; Liu, Juan; Li, Yu‐Xia; Wang, Yan‐Ling (Journal of pineal research, 2023)
Maintaining placental endocrine homeostasis is crucial for a successful pregnancy. Pre‐eclampsia (PE), a gestational complication, is a leading cause of maternal and perinatal morbidity and mortality. Aberrant elevation of testosterone (T 0 ) synthesis, reduced estradiol (E 2 ), and melatonin productions have been identified in preeclamptic placentas. However, the precise contribution of disrupted homeostasis among these hormones to the occurrence of PE remains unknown. In this study, we established a strong correlation between suppressed melatonin production and decreased E 2 as well as elevated T 0 synthesis in PE placentas. Administration of the T 0 analog testosterone propionate (TP; 2 mg/kg/day) to pregnant mice from E7.5 onwards resulted in PE‐like symptoms, along with elevated T 0 production and reduced E 2 and melatonin production. Notably, supplementation with melatonin (10 mg/kg/day) in TP‐treated mice had detrimental effects on fetal and placental development and compromised hormone synthesis. Importantly, E 2 , but not T 0 , actively enhanced melatonin synthetase AANAT expression and melatonin production in primary human trophoblast (PHT) cells through GPER1‐PKA‐CREB signaling pathway. On the other hand, melatonin suppressed the level of estrogen synthetase aromatase while promoting the expressions of androgen synthetic enzymes including 17β‐HSD3 and 3β‐HSD1 in PHT cells. These findings reveal an orchestrated feedback mechanism that maintains homeostasis of placental sex hormones and melatonin. It is implied that abnormal elevation of T 0 synthesis likely serves as the primary cause of placental endocrine disturbances associated with PE. The suppression of melatonin may represent an adaptive strategy to correct the imbalance in sex hormone levels within preeclamptic placentas. The findings of this study offer novel evidence that identifies potential targets for the development of innovative therapeutic strategies for PE.